Small Business Development Strategy Through Go Digital in The Martapura Snakehead Fish Floss Business as a Regional Superior Product - Nurul Wahyuni; Siti Rusidah (Research Synergy Foundation, 2024)
The presence of superior products in a region can significantly boost economic development. In Martapura City, Indonesia, the fisheries and marine sector, supported by a substantial supply capacity, holds potential as a driver of economic growth. A notable example is the snakehead fish processing business, which taps into the region's resources. This research aims to analyze the potential of this business and formulate strategies for developing Snakehead Fish Floss in Martapura through digital marketing. This research uses a qualitative approach with in-depth observation, where primary data was obtained through structured interviews with snakehead fish shredded business actors in Martapura. The research results found that the business potential for snakehead fish floss is very large because there is rarely any difficulty obtaining raw materials. Preparedness and consistency are needed in implementing marketing digitalization in small businesses, and the benefits of digitalization are felt realistically by snakehead fish floss business actors, increasing sales. The results of this research can be generalized to other small businesses because advances in digital technology cannot be avoided at this time.